The Challenges of English Native Speaker in Teaching English in A Junior High School Manokwari West Papua - Winda Sri Handayani; Koesoemo Ratih; Muamaroh Muamaroh (Dinasti International Journal of Education Management And Social Science, 2025)
Teaching English requires effective strategies for students to improve their language skills. English Native Speakers play an important role in the learning process as they provide a more authentic language experience. However, English Native Speakers also face various challenges, especially when teaching in one of the junior high schools in Manokwari, West Papua. This study aims to identify the challenges English Native Speakers face in teaching English in that school. Using a descriptive qualitative approach, data were collected through interviews and classroom observations. The results showed that English Native Speakers experience challenges in dealing with differences in students' ability levels, cultural gaps, and adaptation to the local education system. In addition, large class sizes and limited opportunities for students to practice English outside the classroom are also barriers to learning. By understanding these challenges, it is hoped that teaching strategies can be improved and recommendations made for more effective English language teaching in Manokwari.